2004
DOI: 10.1007/s00421-004-1260-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation characteristics of shoulder muscles during maximal and submaximal efforts

Abstract: Determination of individual maximum voluntary contraction (MVC) force is used as the gold standard for normalising surface EMG (SEMG) data. Assuming a linear amplitude-force relationship, individual strain levels are defined according to percentage rates of the measured MVC levels. The purpose of the study was to investigate if the assumed force-strain relationship can be applied without qualification. Therefore, healthy volunteers (nine men, ten women) were investigated during isometric exercises of shoulder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Disposable pre-gelled EMG Ag-AgCl electrodes (Blue Sensor, Medicotest, Inc., Olstykke, Denmark) with a 2 cm centre-to-centre inter-electrode distance were applied over 8 bilateral muscle groups: Thoracic Erector Spinae (5 cm lateral to T9 spinous process) (Callaghan et al, 1998), Lumbar Erector Spinae (above and below L1 spinous process) (Danneels et al, 2001), Latissimus Dorsi (upper 1/3 of a line connecting the posterior shoulder crease and L1) (Anders et al, 2005), Rectus Abdominus (1 cm above umbilicus and 2 cm lateral to midline) (Ng et al, 1998), Internal Oblique (1 cm medial to ASIS and beneath a line joining bilateral ASIS) (Ng et al, 1998), External Oblique (below the rib cage, along a line connecting the inferior costal margin and the contralateral pubic tubercle) (Ng et al, 1998), Gluteus Medius (1 inch distal to the midpoint of the iliac crest) (Zipp, 1982), and Gluteus Maximus (midway between the greater trochanter and the sacrum) (Zipp, 1982). All electrode placements were confirmed through palpation and manual resistance.…”
Section: Experimental Protocol and Data Collectionmentioning
confidence: 99%
“…Disposable pre-gelled EMG Ag-AgCl electrodes (Blue Sensor, Medicotest, Inc., Olstykke, Denmark) with a 2 cm centre-to-centre inter-electrode distance were applied over 8 bilateral muscle groups: Thoracic Erector Spinae (5 cm lateral to T9 spinous process) (Callaghan et al, 1998), Lumbar Erector Spinae (above and below L1 spinous process) (Danneels et al, 2001), Latissimus Dorsi (upper 1/3 of a line connecting the posterior shoulder crease and L1) (Anders et al, 2005), Rectus Abdominus (1 cm above umbilicus and 2 cm lateral to midline) (Ng et al, 1998), Internal Oblique (1 cm medial to ASIS and beneath a line joining bilateral ASIS) (Ng et al, 1998), External Oblique (below the rib cage, along a line connecting the inferior costal margin and the contralateral pubic tubercle) (Ng et al, 1998), Gluteus Medius (1 inch distal to the midpoint of the iliac crest) (Zipp, 1982), and Gluteus Maximus (midway between the greater trochanter and the sacrum) (Zipp, 1982). All electrode placements were confirmed through palpation and manual resistance.…”
Section: Experimental Protocol and Data Collectionmentioning
confidence: 99%
“…Smoothing techniques and 'peak' extraction from an MVE trial are controversial (Anders et al, 2005). Mathiassen et al (1995) found few studies that reported their methods for extracting peak values from the MVE recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Lifting an absolute load of say 1 kg mass might require 10% of the maximum muscle capacity in a strong individual compared to say 40% of the maximum muscle capacity in another person who is not as strong. It is not possible to estimate maximum muscle activity from a relative submaximal contraction by linear extrapolation because the torque/EMG relationship is nonlinear [96]. Additionally, the lengths of muscle moment arms in individuals vary and since the EMG signal is related to the force produced by the muscle and not the torque produced by the limb, the force required by the muscle to produce a given torque would be different between individuals.…”
Section: Activation Levels During Submaximal Isometric Contractionsmentioning
confidence: 99%